Formal and Informal Strategies for Decreasing Risk: Insurance vs Accumulation of Social Capital - МалковаМария Александровна (Journal of Economic Sociology, 2010)
In contemporary Russia there are some important factors restraining the development of voluntary insurance. Some standard patterns of financial behavior are rejected. Informal strategy of a reliance on social networks successfully competes with the formal insurance programs. Reciprocal relations prove to be an efficient instrument for a distribution of risk among households. The author compares formal strategies of risk reduction implying that individuals address an insurance company with the informal strategies implying that individuals rely on resources mobilized from their social network and the use of social capital.